ChemInform Abstract: Enantioselective Decarboxylative Aldol Addition of β‐Ketoacids to Isatins Catalyzed by Binaphthyl‐Modified Organocatalyst. Issue 42 (1st October 2013) - Suh, Chang Won; Chang, Chul Woo; Choi, Keon Woong; Lim, Young Jo; Kim, Dae Young
Abstract Optimized reaction conditions using a squaric acid diamide derivative as the catalyst are developed for the title reaction to afford phenacyloxindole derivatives with excellent enantioselectivity.